(untitled) (Canadian Allergy & Immunology Today, 2022)
This 3-part series will discuss food allergy prevention in preschool children through early nutrition and eczema management. In Part 1, the prevalence of food allergy along with factors contributing to its rise and its impact on quality of life are presented. Part 2 in this series will examine the topic of food allergy prevention through early infant nutrition and early management of eczema. Finally, in Part 3, we will focus on adverse food reactions in children, symptoms of immunoglobulin E (IgE)-mediated food allergy in preschool children, food-specific IgE testing and management of food allergy.